Predictable Financial Crises - GREENWOOD, ROBIN; HANSON, SAMUEL G.; SHLEIFER, ANDREI; SØRENSEN, JAKOB AHM (Journal of Finance, 2022)
ABSTRACTUsing historical data on postwar financial crises around the world, we show that the combination of rapid credit and asset price growth over the prior three years, whether in the nonfinancial business or the household sector, is associated with a 40% probability of entering a financial crisis within the next three years. This compares with a roughly 7% probability in normal times, when neither credit nor asset price growth is elevated. Our evidence challenges the view that financial crises are unpredictable “bolts from the sky” and supports the Kindleberger‐Minsky view that crises are the byproduct of predictable, boom‐bust credit cycles. This predictability favors policies that lean against incipient credit‐market booms.